PENGARUH INKUBATOR BERSUHU TERKONTROL TERHADAP KECEPATAN DAN KUALITAS FERMENTASI TAPE SINGKONG KHAS JAWA BARAT - Alya Putri Ramadhani; Fely Aprilia; Septi Yana Sabrina; Hypatia Ryma; Anandhava; Eli Trisnowati (PPPM POLTESA, 2026)
This research aims to examine the effect of a temperature-controlled incubator on the speed and quality of cassava tape fermentation compared to room-temperature fermentation. The incubator was constructed using a styrofoam box reinforced with cardboard, a light bulb as a heat source, and a digital thermostat for temperature regulation. The method involved visual observations of color, texture, and maturity level during fermentation under two conditions: fermentation using the incubator and fermentation at room temperature. The results showed that cassava tape fermented in the incubator reached optimal maturity within 40 hours, whereas room-temperature fermentation required 72 hours. This substantial difference indicates that stable temperature enhances the enzymatic activity of yeast, leading to faster and more uniform fermentation. Tape produced using the incubator exhibited more homogeneous yellow coloration, a softer texture, and consistent maturity, while tape fermented without an incubator showed uneven ripening. Therefore, the simple incubator effectively accelerates fermentation and improves product quality, making it a low-cost technological solution suitable for household-scale and micro-enterprise applications.